The effect of exposure to liquid air freshener on histological of the bronchial mice (Mus musculus) - Warobi, Warobi (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2021)
Air fresheners are products that contain chemicals aimed at reducing unpleasant odours in confined spaces. The use of synthetic air fresheners turns out to harm health because some of their leased Volatile Organic Compounds are classified as toxic compounds and are carcinogens. Air freshener enters the body through the inhalation process in the respiratory system. Modern air fresheners are available in liquid (aerosol) and gel forms. Air fresheners contain addictive substances and solvents such as 1,4-dichlorobenzene which can affect pulmonary function. The purpose of this study is to know the effect of exposure to liquid air freshener on the histology of bronchi of mice (Mus musculus). This study used 20 male mice (Mus musculus) consisting of 4 treatments with 5 replications. The research design is true experimental in the form of a post-test only control group with Completely Randomized Design (CRD). The post-test was done by observing the histological picture of the mice's bronchi after exposure to liquid air freshener given 3x/day for a period of P1 = 2 weeks, P2 = 4 weeks and P3 = 6 weeks. Quantitative data on bronchial histology was tested using the One Way ANOVA statistical test followed by the Post Hoc Tukey test. The results of the study found changes in the histology of the bronchi, thickening of the epithelial tissue of mice. Analysis of comparative data between the control and treatment groups statistically obtained p = 0.010 <0.05, meaning that there was a significant effect and change in the bronchial tubes exposed to liquid air freshener. Histologically there were differences in histology between the control and treatment groups. It was concluded that liquid air freshener had a significant effect on the histological picture of the mice's bronchi.